THE ANALYSIS OF TEXT TO TEXT FROM READING COMPREHENSION MADE BY JUNIOR HIGH SCHOOL STUDENTS - Al Fithoni, Nasih Jadid; Tjendani, Endah Nur; Nughraheni, Dyah Ayu (FKIP Universitas Islam Jember, 2022)
This study is designed to analyze descriptive texts of junior high school. This research was conducted using discourse analysis method. By means of the researcher giving a descriptive text, then students are asked to read the text, then students are asked to write with their own language. The researchers analyzed the results of the student's writing on the language features and generic structure of the descriptive text. This study reveals the problems of students in writing descriptive text again in their own language. Where students have difficulty in the process of rewriting what they have read before, starting from word structure, grammar, and vocabulary. The findings of this study are to improve the data in the basic material of writing descriptive texts, especially in the fields of language and education. Keywords: descriptive text, generic structure, language features.